2016
DOI: 10.1186/s12993-016-0093-0
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of bone marrow-derived mesenchymal stem cells (BMSCs) improves brain ischemia-induced pulmonary injury in rats associated to TNF-α expression

Abstract: BackgroundBone marrow mesenchymal stem cell (BMSCs)-based therapy seems to be a promising treatment for acute lung injury, but the therapeutic effects of BMSCs transplantation on acute lung injury induced by brain ischemia and the mechanisms have not been totally elucidated. This study explores the effects of transplantation of BMSCs on acute lung injury induced by focal cerebral ischemia and investigates the underlying mechanism.MethodsAcute lung injury model was induced by middle cerebral artery occlusion (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In previous studies, it was found that the growth status of BMSCs in passage 3 was better than that in passage 1 or 2 (25,26). Therefore, BMSCs at passage 3 were used in this study.…”
Section: Methodsmentioning
confidence: 95%
“…In previous studies, it was found that the growth status of BMSCs in passage 3 was better than that in passage 1 or 2 (25,26). Therefore, BMSCs at passage 3 were used in this study.…”
Section: Methodsmentioning
confidence: 95%
“…Primary BMSCs were acquired as described previously [20]. In brief, the femur and tibias of SD rats were carefully separated and washed with phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow-derived mesenchymal stem cells (BMSCs) possess pluripotency during several passages, and are commonly acceptable for differentiation into many cell types, such as chondrocytes and osteoblasts [9-11]. Transplantation of BMSCs has been widely studied as promising treatments for ischemia-induced pulmonary injury [12], pelvic floor dysfunction [13] and olfactory disorder [14]. In terms of orthopaedic researches, BMSCs are proved to facilitate cartilage regeneration because of the rapid cell proliferation, multipotency and easy isolation [15].…”
Section: Introductionmentioning
confidence: 99%
“…The BMSCs differentiate into cardiomyocytes and replace the apoptotic myocardium thereby improving the function of damaged hearts [ 9 ]. They are critical for immunomodulatory function, inflammatory response and epithelial function [ 10 ]. However, the poor long-term survival of transplanted MSCs presents a major therapeutic problem that needs to be overcome [ 11 ].…”
Section: Introductionmentioning
confidence: 99%